Modelling wheat (Triticum aestivum) production at state level in post-green revolution era - PRAJNESHU, PRAJNESHU; DAS, P K (The Indian Journal of Agricultural Sciences, 2013)
Non-linear mechanistic growth models, viz monomolecular, logistic, Gompertz., mixed-influence and Richards, were used for describing’state-wise, production-data of wheat (Triticum aestivum L. emend. Fiori & Paol.) during 1966-67 to 1992-93. The parameters of these models were estimated using Levenberg-Marquardt procedure for nonlinear estimation. The 6 major wheat-growing states considered are Punjab, Haryana. Uttar Pradesh, Madhya Pradesh, Rajasthan and Bihar. For each of these’ states, logistic model described quite well the wheat-production data in the post green-revolution cra. A comparative performance of various states for wheat production. showed that Haryana’s perfoemance is the best, as reflected by its high intrinsic growth rate and as it is still in the fast phase of growth, which is likely to continue in near future also in view of the current trend.